The catalytic domain of the histone methyltransferase NSD2/MMSET is required for the generation of B1 cells in mice. Issue 20 (29th August 2020) - Dobenecker, Marc‐Werner; Marcello, Jonas; Becker, Annette; Rudensky, Eugene; Bhanu, Natarajan V.; Carrol, Thomas; Garcia, Benjamin A.; Prinjha, Rabinder; Yurchenko, Vyacheslav; Tarakhovsky, Alexander
Abstract : Humoral immunity in mammals relies on the function of two developmentally and functionally distinct B‐cell subsets—B1 and B2 cells. While B2 cells are responsible for the adaptive response to environmental antigens, B1 cells regulate the production of polyreactive and low‐affinity antibodies for innate humoral immunity. The molecular mechanism of B‐cell specification into different subsets is understudied. In this study, we identified lysine methyltransferase NSD2 (MMSET/WHSC1) as a critical regulator of B1 cell development. In contrast to its minor impact on B2 cells, deletion of the catalytic domain of NSD2 in primary B cells impairs the generation of B1 lineage. Thus, NSD2, a histone H3 K36 dimethylase, is the first‐in‐class epigenetic regulator of a B‐cell lineage in mice. Abstract :